Negative electrode lead paste for enhancing low-temperature performance of lead-acid storage battery and preparation method of negative electrode lead paste
By adding UiO@C expansion agent to the negative lead paste of lead acid battery, the problem of poor low temperature performance of lead acid battery is solved, and better low temperature performance and battery performance are achieved.
Patent Information
- Application Number
- CN202411576143.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
The poor low-temperature performance of lead-acid batteries has limited applications in the northern market.
A new type of negative electrode lead paste is used, and the UiO@C expansion agent is added. By adding UiO@C expansion agent with a metal organic frame structure to the negative electrode lead paste, the low-temperature performance of lead acid batteries is improved.
It effectively improves the low-temperature performance of lead-acid batteries, reduces internal resistance, delays the passivation of the negative electrode plate, and enhances the overall performance of the battery.
Smart Images

Figure CN119447283A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lead-acid batteries, and in particular relates to a negative electrode lead paste for enhancing the low-temperature performance of a lead-acid battery and a preparation method thereof. Background Art
[0002] At present, lead-acid batteries are widely used in automobiles, electric vehicles, communications, and power transmission due to their high safety, low cost, and recyclable raw materials. The low-temperature capacity of lead-acid batteries is a key performance indicator, but poor low-temperature performance has hindered the application of lead-acid batteries in the northern market. The low-temperature performance of lead-acid batteries mainly depends on the negative plate. Since the negative plate will shrink and passivate at low temperatures, adding appropriate expansion agents to prevent the shrinkage and passivation of the negative plate is one of the main solutions.
[0003] At present, lignin is mainly used as an expander to prevent the shrinkage and passivation of the negative plate of lead-acid batteries at low temperatures. Lignin is a type of anionic surfactant that is easily adsorbed on the negative sponge metal lead with a large surface area. When sodium lignin sulfonate is adsorbed on the negative sponge metal lead, the surface energy of the negative electrode can be reduced, thereby inhibiting the surface shrinkage of the negative electrode active material during the charge and discharge cycle, maintaining the porosity and high dispersion of the negative sponge metal lead, and improving the electrochemical performance of the negative electrode. Especially at high rate discharge and low temperature discharge, it delays the passivation of the negative electrode. However, lignin has poor thermal stability, is unstable at high temperatures, and decomposes during charging. Therefore, an expander with excellent thermal stability is needed to improve the low temperature performance of lead-acid batteries. Summary of the invention
[0004] One of the purposes of the present invention is to provide a negative lead paste for enhancing the low temperature performance of a lead-acid battery, so as to solve the problem that the low temperature performance of the lead-acid battery is poor;
[0005] A second object of the present invention is to provide a method for preparing a negative electrode lead paste for enhancing the low temperature performance of a lead-acid battery.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] In a first aspect, a negative lead paste for enhancing the low temperature performance of a lead-acid battery comprises the following components in parts by weight:
[0008] 100 parts of lead powder, 0.1-0.2 parts of barium sulfate, 0.01-0.05 parts of humic acid, 0.01-0.005 parts of carbon black, 0.005-0.02 parts of short fibers, 1-10 parts of water, 0.01-0.05 parts of UiO@C expansion agent;
[0009] The density of the negative electrode lead paste is 4.2-4.8 g / cm 3 .
[0010] Furthermore, the preparation method of the UiO@C expansion agent comprises the following steps:
[0011] S1. Add a zirconium source to DMF (N,N-dimethylformamide), mix well to obtain a zirconium salt solution; add BPDC (biphenyl-4,4'-dicarboxylic acid) to DMF, mix well to obtain a BPDC solution;
[0012] S2. The zirconium salt solution and the BPDC solution are mixed evenly and allowed to react. After the reaction is completed, the UiO powder is collected by centrifugation;
[0013] S3. placing UiO powder in a carbon source and carbonizing it under a protective atmosphere to obtain a UiO@C precursor;
[0014] S4. The UiO@C precursor is immersed in a nitric acid solution for etching, and then centrifuged to obtain a UiO@C expander.
[0015] Further, the zirconium source is selected from any one of zirconium sulfate tetrahydrate (Zr(SO4)2﹒4H2O), zirconium chloride (ZrCl4), and zirconium nitrate pentahydrate (Zr(NO3)4﹒5H2O);
[0016] Furthermore, the molar ratio of the zirconium source to BPDC is 0.02-0.2 mol: 0.02-2 mol; preferably, the molar ratio of the zirconium source to BPDC is 0.05-0.1 mol: 0.08-0.12 mol.
[0017] Furthermore, the carbon source is urea (CO(NH2)2) or melamine (C3H6N6); preferably, the carbon source is melamine.
[0018] Furthermore, the carbonization temperature is 300-800°C; preferably, the carbonization temperature is 400-500°C.
[0019] Furthermore, the concentration of the nitric acid solution is 0.05-0.5 mol / L; preferably, the concentration of the nitric acid solution is 0.1 mol / L.
[0020] Furthermore, the etching time is 20-60 min; preferably, the etching time is 20-40 min.
[0021] In a second aspect, a method for preparing a negative lead paste for enhancing the low temperature performance of a lead-acid battery comprises the following steps:
[0022] Step 1: Evenly mix barium sulfate, humic acid, carbon black, short fibers and water under stirring to form a mixture A;
[0023] Step 2, adding mixture A to the lead powder and mixing evenly to obtain mixture B;
[0024] Step 3: Add UiO@C expander into mixture B and stir evenly to obtain negative electrode lead paste.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The invention provides a negative electrode lead paste for enhancing the low temperature performance of a lead-acid battery and a preparation method thereof. By adding a novel metal organic framework structure UiO@C expander into the negative electrode lead paste, the low temperature performance of the lead-acid battery is effectively improved, thereby contributing to the widespread use of lead-acid batteries in the northern market.
[0027] By synthesizing a UiO@C expander with a metal organic framework structure, it has the advantages of excellent thermal stability, large specific surface area and low internal resistance. The large specific surface area can prevent the shrinkage and passivation of the negative plate, the low internal resistance can reduce the internal resistance of the lead-acid battery and improve the performance of the lead-acid battery, and the excellent thermal stability can avoid its own decomposition when the battery temperature rises (when charging), and then it can play its role at low temperatures. Adding it to the negative lead paste, replacing the traditional lignin as an expander, can not only reduce the internal resistance of the lead-acid battery, but also improve the low-temperature performance of the lead-acid battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The present invention will be further described below in conjunction with the accompanying drawings.
[0029] Figure 1 It is the schematic diagram of the equivalent circuit in the battery impedance test;
[0030] Figure 2 It is a comparison chart of impedance test results of lead-acid batteries made of the negative electrode lead paste prepared in Example 2 of the present invention and the negative electrode lead paste prepared in Comparative Example 1;
[0031] Figure 3 The polarization curves of hydrogen evolution reaction of negative electrode plates of lead-acid batteries made from the negative electrode paste prepared in Example 2 of the present invention and the negative electrode paste prepared in Comparative Example 1 are compared. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The preparation method of UiO@C expansion agent comprises the following steps:
[0034] S1. Add 0.02-0.2 mol of zirconium source to 250 mL of DMF and stir at 250 rpm using a magnetic stirring instrument to obtain a zirconium salt solution; add 0.02-0.2 mol of BPDC to 250 mL of DMF and stir at 250 rpm using a magnetic stirring instrument to obtain a BPDC solution;
[0035] S2. The zirconium salt solution and the BPDC solution were stirred and mixed evenly and then allowed to react for 2-8 hours. After the reaction was completed, the reaction solution was centrifuged at 8000 rpm using a high-speed centrifuge to collect the yellow powder UiO powder;
[0036] S3. The UiO powder is placed in a carbon source and carbonized at 300-800°C under a protective atmosphere to obtain a black powder UiO@C precursor;
[0037] S4. The UiO@C precursor is immersed in a 0.05-0.5 mol / L nitric acid solution for etching for 20-60 min, and then centrifuged to obtain a UiO@C expansion agent.
[0038] In a specific implementation case, the zirconium source is selected from any one of Zr(SO4)2﹒4H2O, ZrCl4, and Zr(NO3)4﹒5H2O.
[0039] In a specific implementation case, the carbon source is urea or melamine.
[0040] A negative lead paste for enhancing the low temperature performance of a lead-acid battery comprises the following components in parts by weight:
[0041] 100 parts of lead powder, 0.1-0.2 parts of barium sulfate, 0.01-0.05 parts of humic acid, 0.01-0.005 parts of carbon black, 0.005-0.02 parts of short fibers, 1-10 parts of water, 0.01-0.05 parts of UiO@C expansion agent;
[0042] The density of the negative electrode lead paste is 4.2-4.8 g / cm 3 .
[0043] The method for preparing the negative electrode lead paste comprises the following steps:
[0044] Step 1, under stirring at 200 rpm, 0.1-0.2 parts of barium sulfate, 0.01-0.05 parts of humic acid, 0.01-0.005 parts of carbon black, 0.005-0.02 parts of short fibers, and 1-10 parts of water are mixed to form a mixture A;
[0045] Step 2, adding mixture A to 100 parts of lead powder, and mixing evenly to obtain mixture B;
[0046] Step 3: Add 0.01-0.05 parts of UiO@C expansion agent into mixture B by high pressure spraying, and stir evenly to obtain a density of 4.2-4.8 g / cm 3 Negative electrode lead paste.
[0047] Example 1
[0048] The preparation method of UiO@C expansion agent comprises the following steps:
[0049] S1. Add 0.08 mol Zr(SO4)2﹒4H2O to 250 mL DMF and stir at 250 rpm using a magnetic stirring instrument to obtain a zirconium salt solution; add 0.01 mol BPDC to 250 mL DMF and stir at 250 rpm using a magnetic stirring instrument to obtain a BPDC solution;
[0050] S2. The zirconium salt solution and the BPDC solution were stirred and mixed evenly and then allowed to react for 6 hours. After the reaction was completed, the reaction solution was centrifuged at 8000 rpm using a high-speed centrifuge to collect the yellow powder UiO powder;
[0051] S3. The UiO powder was placed in melamine and carbonized at 450°C under an argon atmosphere to obtain a black powder UiO@C precursor;
[0052] S4. The UiO@C precursor was immersed in a 0.1 mol / L nitric acid solution for etching for 30 min, and then centrifuged to obtain a UiO@C expansion agent.
[0053] The UiO@C expansion agents in the following examples and comparative examples are all prepared in this example.
[0054] Example 2
[0055] A negative lead paste for enhancing the low temperature performance of a lead-acid battery comprises the following components in parts by weight:
[0056] 100 parts of lead powder, 0.15 parts of barium sulfate, 0.03 parts of humic acid, 0.008 parts of carbon black, 0.01 parts of short fibers, 8 parts of water, and 0.03 parts of UiO@C expansion agent;
[0057] The density of the negative electrode lead paste is 4.6 g / cm 3 .
[0058] The method for preparing the negative electrode lead paste comprises the following steps:
[0059] Step 1, under stirring condition of 200 rpm, barium sulfate, humic acid, carbon black, short fibers and water are mixed uniformly to form a mixture A;
[0060] Step 2, adding mixture A to the lead powder and mixing evenly to obtain mixture B;
[0061] Step 3: Add the UiO@C expander into the mixture B by high-pressure spraying, and stir evenly to obtain the negative electrode lead paste.
[0062] Comparative Example 1
[0063] A negative electrode lead paste for a lead-acid battery, comprising the following components in parts by weight:
[0064] 100 parts of lead powder, 0.15 parts of barium sulfate, 0.03 parts of humic acid, 0.008 parts of carbon black, 0.01 parts of short fibers, 8 parts of water, and 0.03 parts of lignin expansion agent;
[0065] The method for preparing the negative electrode lead paste comprises the following steps:
[0066] Step 1, under stirring condition of 200 rpm, barium sulfate, humic acid, carbon black, short fibers and water are mixed uniformly to form a mixture A;
[0067] Step 2, adding mixture A to the lead powder and mixing evenly to obtain mixture B;
[0068] Step 3: Add the lignin expander into the mixture B by high-pressure spraying, and stir evenly to obtain the negative electrode lead paste.
[0069] Performance Testing:
[0070] The negative electrode lead pastes prepared in Example 2 and Comparative Example 1 were respectively coated, cured, assembled, and formed to produce lead-acid batteries (12V 25Ah):
[0071] The impedance of the two batteries was tested, and the obtained impedance data was fitted. The equivalent circuit is as follows: Figure 1 The fitting results show that the negative electrode lead paste (Example 2) with the UiO@C expander prepared in Example 1 has an R1 (internal resistance) of 9.4554mΩ and an R2 (charge transfer resistance) of 5.7217mΩ; while the negative electrode lead paste (Comparative Example 1) with the lignin additive has an R1 of 9.6171mΩ and an R2 of 7.0247mΩ; the impedance test results are shown in Figure 2 As shown; by comparison, it can be seen that, whether it is R1 or R2, the lead-acid battery using the negative lead paste with the UiO@C expander prepared in Example 1 is smaller than the lead-acid battery using lignin. This shows that the lead-acid battery made of the negative lead paste using the UiO@C expander has a smaller impedance and can then exert a better low-temperature performance.
[0072] Next, the two batteries were subjected to a low-temperature capacity test, and the batteries were discharged at a current of 3 hr capacity (8.33 A). The test results showed that the capacity of the lead-acid battery with the UiO@C expander prepared in Example 1 at -10°C was 23.614 Ah (0.94C), while the capacity of the lead-acid battery with lignin at -10°C was 21.923 (0.88C), indicating that the lead-acid battery manufactured using the UiO@C expander has better low-temperature performance.
[0073] At the same time, the negative plate of the lead-acid battery was tested for hydrogen evolution performance. The test results are as follows: Figure 3 As can be seen from the figure, compared with the plate made using the lignin expander, the plate made using the negative electrode lead paste to which the UiO@C expander prepared in Example 1 is added has a larger hydrogen evolution overpotential. The larger the hydrogen evolution overpotential, the more difficult it is for the hydrogen evolution reaction to occur. This indicates that the plate made using the negative electrode lead paste to which the UiO@C expander is added is more difficult to undergo a hydrogen evolution side reaction and has a better battery performance.
[0074] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0075] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A negative electrode lead paste for enhancing the low temperature performance of a lead-acid battery, characterized in that: In parts by weight, it includes the following components: 100 parts of lead powder, 0.1-0.2 parts of barium sulfate, 0.01-0.05 parts of humic acid, 0.01-0.005 parts of carbon black, 0.005-0.02 parts of short fibers, 1-10 parts of water, 0.01-0.05 parts of UiO@C expansion agent; The density of the negative electrode lead paste is 4.2-4.8 g / cm 3 .
2. The negative electrode lead paste for enhancing the low temperature performance of a lead-acid battery according to claim 1, characterized in that: The preparation method of the UiO@C expansion agent comprises the following steps: S1. The zirconium source was added to DMF and mixed to obtain a zirconium salt solution; BPDC was added to DMF and mixed to obtain a BPDC solution; S2. The zirconium salt solution and the BPDC solution are mixed evenly and allowed to react. After the reaction is completed, the UiO powder is collected by centrifugation; S3. placing the UiO powder in a carbon source and carbonizing it under a protective atmosphere to obtain a UiO@C precursor; S4. The UiO@C precursor is immersed in a nitric acid solution for etching, and then centrifuged to obtain a UiO@C expander.
3. The negative electrode lead paste for enhancing the low temperature performance of a lead-acid battery according to claim 2, characterized in that: The zirconium source is selected from any one of zirconium sulfate tetrahydrate, zirconium chloride and zirconium nitrate pentahydrate.
4. The negative electrode lead paste for enhancing the low temperature performance of a lead-acid battery according to claim 2, characterized in that: The molar ratio of the zirconium source to BPDC is 0.02-0.2 mol: 0.02-2 mol.
5. The negative electrode lead paste for enhancing the low temperature performance of a lead-acid battery according to claim 2, characterized in that: The carbon source is urea or melamine.
6. The negative electrode lead paste for enhancing the low temperature performance of a lead-acid battery according to claim 2, characterized in that: The carbonization temperature is 300-800°C.
7. The negative electrode lead paste for enhancing the low temperature performance of a lead-acid battery according to claim 2, characterized in that: The concentration of the nitric acid solution is 0.05-0.5 mol / L.
8. The negative electrode lead paste for enhancing the low temperature performance of a lead-acid battery according to claim 2, characterized in that: The etching time is 20-60 minutes.
9. A method for preparing a negative electrode lead paste for enhancing the low temperature performance of a lead-acid battery as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Evenly mix barium sulfate, humic acid, carbon black, short fibers and water under stirring to form a mixture A; Step 2, adding mixture A to the lead powder and mixing evenly to obtain mixture B; Step 3: Add UiO@C expander into mixture B and stir evenly to obtain negative electrode lead paste.